Mercury flow analysis and reduction pathways for fluorescent lamps in mainland China. (1st October 2016) - Zhang, Jiaxing; Chen, Sha; Kim, Junbeum; Cheng, Shuiyuan
Abstract: China is one of the largest consumers and producers of fluorescent lamps in the world, and mercury from a large number of spent fluorescent lamps can enter the solid waste stream every year. However, detailed information about the quantity and the fate of mercury caused by fluorescent lamps is unavailable. This study quantified and determined the fate and flow of mercury in fluorescent lamps from manufacture to disposal using the material flow analysis (MFA) method. Indirect mercury emissions, which were from coal consumption during the use phase, were calculated. The pathways for mercury reduction were also discussed. It was estimated that the mercury contained in fluorescent lamps for domestic production, export and import in 2011 was 29.31, 12.81 and 3.95 tons, respectively. The mercury in the domestic usage category was 20.45 tons, of which 3.89 tons was sent for incineration and 15.54 tons was sent to landfill at the end-of-life phase, but only 0.97 tons of mercury was recovered. During the use phase, 27.51 tons of mercury was released to the atmosphere, and 11.79 tons was released to the land. The total amount of mercury emissions to the atmosphere and land was 28.31 and 30.47 tons, respectively. Manufacturing low-mercury-content lamps, reducing coal consumption during the generation of electricity and increasing the recycling rate of lamps can all significantly reduce mercury emissions to the environment. Highlights: The fate and flow of mercury caused by fluorescent lamps was investigated. Indirect mercury emissions, which were from the use phase, were calculated. The potential pathways for mercury reduction were discussed.